Stress (Nabr) in Arabic Text Reading: A Study of Arabic Language and Literature Students at UIN Syarif Hidayatullah Jakarta - Hadi Kusuma, Allisya Putri (Fakultas Adab dan Humaniora, Universitas Islam Negeri Syarif Hidayatullah Jakarta, 2025)
This study aims to analyze how students of Arabic Language and Literature at the Faculty of Adab and Humanities, Syarif Hidayatullah State Islamic University Jakarta, apply stress (nabr) when reading Arabic texts written by Muhammad ‘Anani. To clarify this issue, the study employs a descriptive-analytical method by collecting, classifying, and analyzing data obtained directly from students through interviews. Out of 48 words and 198 syllables tested on 25 students, 22 students achieved scores of more than 50 percent, while the remaining three students obtained percentages below this threshold. These findings indicate that the application of stress (nabr) among students of Arabic Language and Literature at the Faculty of Adab and Humanities, Syarif Hidayatullah State Islamic University Jakarta is not entirely consistent or uniform, and that some instances still do not conform to the prescribed rules that have been taught.